The state of oral mucosa in patients with type 2 diabetes - Shnaider, S. A.; Skyba, V. Ya.; Skyba, O. V.; Babenya, H. O.; Varzhapetian, S. D. (Medicni Perspektivi, 2020)
Aspects of the relationship between somatic and dental diseases are multifaceted. The bi-directional, mutually aggravating nature of the relationship between somatic and dental pathology is exemplified by diabetes mellitus. Numerous studies indicate that uncontrolled diabetes contributes to a multiple increase in the risk of caries and tooth loss, damage to the salivary glands, periodontium and oral mucosa. Given that diabetes affects all the main components of the etiology and pathogenesis of dental diseases, the urgent task of dentistry is to develop adequate methods for the treatment and prevention of dental pathology due to the presence of diabetes in the patient, which cannot be done without assessing the dental status of patients in this category. The purpose of the study was a comparative assessment of the state of oral tissues in patients with type 2 diabetes and in people of the similar age without somatic pathology. We examined 70 patients aged 34-48 years, of which 35 patients with type 2 diabetes and 35 healthy individuals of the similar age. Recruitment of patients with diabetes was carried out on the basis of the Communal non-profit enterprise "Odessa Regional Endocrinological Dispensary." All patients were clinically and radiologically examined. It was shown that the prevalence and intensity of the carious process in people with diabetes did not differ from the control group, however, the “M” component prevailed in the structure of the DMF index, the need for prosthetics was 79.1%. Hygiene was by 21.8% worse. All patients with diabetes were diagnosed with generalized periodontitis with the prevalence of an exacerbated course (25.7% more) and a direct dependence of the severity of periodontitis from the degree of decompensation of diabetes. Periodontal indices in patients with diabetes were increased: PMA index – by 70.6%, bleeding index – by 2 times, Russell index – by 1.9 times. In 63.6% of patients with diabetes, changes in the oral mucosa were noted. 25.7% of patients noted the development of candidal stomatitis / glossitis in the past. The functional activity of the salivary glands was reduced by 38.1%. Microcrystallization of saliva in patients with diabetes is represented mainly by IV and V classes according to Leus-Kukina, which indicates its reduced mineralizing ability and the maximum risk of tooth decay.